Peralihan dan pengekalan Bahasa Tamil dalam kalangan masyarakat Tamil di Kuching, Sarawak / Selvajothi @ Pillai Ramalingam - Selvajothi @ Pillai , Ramalingam (2017)
This study focuses the phenomenon of language shift and maintenance of Tamils in Kuching, Sarawak. The study conducted to identify the actual situation of the Tamil language practices in determining the occurrence of language transition. The main objective of this study was to examine the level of Tamil language usage and the ethnolinguistic factors that influence the language shift and maintenance phenomenon of Tamil language in Kuching. Ethnolinguistic Vitality Theory (Giles et al., 1977) was used to analyse the data that was collected via secondary resources such as Statistical Department of Malaysia, reports from the state government, websites, newspapers, magazines, interviews of leaders, journals, books and researcher’s observation. The theoretical framework consists of two approaches namely, sociological and social-psychological approach (data was analysed via Domain Analysis Theory by Fishman, 1972) that could affect the vitality of a language, thereby reflecting the language situation whether to move towards transition or maintenance. This study utilised the mix methodology of quantitative and qualitative technique (Creswell, 2014). The totals of five instruments were used to determine the patterns of language usage. Among them were the questionnaires (254 respondents), interviews (13 informants), audio recordings (41 recordings), observations (14 events) and research documents (15 documents). In furtherance of identify entholinguistic factors, Instruments such as surveys, reports, government documents and observations were used. The data collected from these instruments have provided an overview of the state of Tamil language and identity that either could be maintained or not in the situation of intergroup relation in Kuching. As for the socio-psychology, the use of Tamil language among Kuching Tamils is moderate level. The findings showed that the use of the Tamil language has high vitality in two main domains which are religion and family domain. Generally, domains that are based on the religions and cultural activities have recorded a high level of vitality. These findings are accurate with the findings obtained in respect to the sociology based on a theoretical framework of Ethnolinguistic Vitality that also recorded moderate level. Under the sociological approach, factors such as geographical and institutional support which plays an important role in the maintenance of Tamil language in Kuching. On the other hand, status and demographic factor have weakened the position of the Tamil language in Kuching. The geographical factor ensures high vitality due to benefit received from Tamils in Peninsula of Malaysia. The present study concluded that the vitality of the Tamil language showed by the Tamil community in Kuching is still satisfactory due to moderate level of usage. Tamil people are aware with the fact that English and Malay are important languages for education and employment. However, they still apply Tamil language as the language of cultural heritage and religion practices. In addition, vitality is also influenced by the linguistic identity displayed by them such code switching, dioglosic variation, phonological variation, lexical variation, cultural terms, kinship terms and linguistic landscape which distinguish the Tamil community group from other ethnic groups in Sarawak and also other Tamils from peninsula of Malaysia. collected from these instruments have provided an overview of the state of Tamil language and identity that either could be maintained or not in the situation of intergroup relation in Kuching. As for the socio-psychology, the use of Tamil language among Kuching Tamils is moderate level. The findings showed that the use of the Tamil language has high vitality in two main domains which are religion and family domain. Generally, domains that are based on the religions and cultural activities have recorded a high level of vitality. These findings are accurate with the findings obtained in respect to the sociology based on a theoretical framework of Ethnolinguistic Vitality that also recorded moderate level. Under the sociological approach, factors such as geographical and institutional support which plays an important role in the maintenance of Tamil language in Kuching. On the other hand, status and demographic factor have weakened the position of the Tamil language in Kuching. The geographical factor ensures high vitality due to benefit received from Tamils in Peninsula of Malaysia. The present study concluded that the vitality of the Tamil language showed by the Tamil community in Kuching is still satisfactory due to moderate level of usage. Tamil people are aware with the fact that English and Malay are important languages for education and employment. However, they still apply Tamil language as the language of cultural heritage and religion practices. In addition, vitality is also influenced by the linguistic identity displayed by them such code switching, dioglosic variation, phonological variation, lexical variation, cultural terms, kinship terms and linguistic landscape which distinguish the Tamil community group from other ethnic groups in Sarawak and also other Tamils from peninsula of Malaysia.